Precommercial thinning stumps' susceptibility to Heterobasidion spp. - Mc Carthy, Rebecka (2011)
Each year, Heterobasidion spp. is a major cause of economic losses to forestry in the northern hemisphere, including Sweden. New results indicate that pre‐commercial thinnings could be at risk for Heterobasidion spp. infections. Since no wood usually is used from pre‐commercial thinnings, there would not be any timber losses from leaving high stumps instead of low stumps when carrying out this measure. It could therefore be of a great interest if the stump height, of both Norway spruce (Picea abies (L.) Karst.) and birch (Betula spp.), affects the susceptibility to Heterobasidion spp. after a pre‐commercial thinning is performed.